2020
DOI: 10.1128/jcm.01134-20
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and Clinical Comparison of Three Nucleic Acid Amplification Tests for SARS-CoV-2 Detection

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) was first identified in December 2019 and has quickly become a worldwide pandemic. In response, many diagnostic manufacturers have developed molecular assays for SARS-CoV-2 under the Food and Drug Administration (FDA) Emergency Use Authorization (EUA) pathway. This study compared 3 of these assays: the Hologic Panther Fusion SARS-CoV-2 assay (Fusion), the Hologic Aptima SARS-CoV-2 assay (Aptima) and the BioFire Defense COVID-19 test (BioFire), to det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 9 publications
(15 reference statements)
8
45
0
Order By: Relevance
“…These analytical sensitivity values correlate with previously reported LOD values by Smith et al (16). However, using LOD values as determined by external control material to assess or compare assay performance warrants some caution, as different control materials may give considerably different results for the absolute LOD value (16), and the reported RNA or DNA stock concentrations of these materials may differ from true concentrations (17). The limitations of this study include the small number of clinical specimens available for testing and the absence of discordant result resolution by testing with a third assay.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These analytical sensitivity values correlate with previously reported LOD values by Smith et al (16). However, using LOD values as determined by external control material to assess or compare assay performance warrants some caution, as different control materials may give considerably different results for the absolute LOD value (16), and the reported RNA or DNA stock concentrations of these materials may differ from true concentrations (17). The limitations of this study include the small number of clinical specimens available for testing and the absence of discordant result resolution by testing with a third assay.…”
Section: Discussionsupporting
confidence: 91%
“…Our evaluation of three different external RNA control materials demonstrated comparable analytical sensitivity with both the SARS-CoV-2 TMA assay and the SARS-CoV-2 RT-PCR assay, with LOD values of between 83 c/ml of 194 c/ml. These analytical sensitivity values correlate with previously reported LOD values by Smith et al (16). However, using LOD values as determined by external control material to assess or compare assay performance warrants some caution, as different control materials may give considerably different results for the absolute LOD value (16), and the reported RNA or DNA stock concentrations of these materials may differ from true concentrations (17).…”
Section: Discussionsupporting
confidence: 83%
“…Although the intended use of the Aptima SARS-CoV-2 is limited to diagnostic materials from the upper respiratory tract, SARS-CoV-2 RNA was detected with 100 % PPA and 99.0 % NPA. These results compared favorably to other studies, which had only included nasopharyngeal swabs (94.7 % to 100 % PPA and 98.7 % to 100 % NPA) (28)(29)(30). However, detection of SARS-CoV-2 in materials from the LRT is crucial as it was shown that nasopharyngeal swabs may turn negative in the course of infection prior to specimens from the LRT (16,(31)(32)(33).…”
Section: Amplification Efficiencies and Lodsupporting
confidence: 59%
“…Testing for SARS-CoV-2 infection at CSVS clinics began on June 15, 2020, and was offered to all persons at clinics during weekday business hours. Medical personnel collected oropharyngeal specimens for detection of SARS-CoV-2 RNA via the qualitative Aptima SARS-CoV-2 Assay (Hologic, https://www.hologic.com ), a nucleic acid transcription-mediated amplification (TMA) assay with an analytical sensitivity of 62.5 RNA transcript copies/mL ( 17 ) and clinical specificity of 99.9% ( 18 ). Patients receiving care from CSVS for any reason were encouraged by their healthcare providers to receive SARS-CoV-2 testing, regardless of symptoms; testing also was made available to persons who were not CSVS patients.…”
Section: Methodsmentioning
confidence: 99%